Signatures of anti-Thomsen — friedenreich antigen antibody diversity in colon cancer patients - Kurtenkov, O.; Bubina, M.; Klaamas, K. (Experimental Oncology, 2018)
Aim: To determine whether the structural and functional diversities of naturally occurring antibodies to the Thomsen — Friedenreich (TF) antigen may be of diagnostic and prognostic value in colon cancer. Materials and Methods: Serum samples were taken from patients with colon cancer (n = 94) and healthy controls (n = 64). The level of TF-specific antibody isotypes and their sialylation were determined using ELISA and lectin-ELISA with synthetic TF-polyacrylamide conjugate as an antigen and a sialic acid-specific Sambucus nigra agglutinin (SNA). The avidity was determined using ammonium thiocyanate as a chaotrope. The accuracy of diagnostics was evaluated using the receiver operator characteristic curve analysis and the survival analysis employing the Kaplan — Meier method. Results: Compared to healthy controls, patients with colon cancer exhibited a lower level of anti-TF IgG antibodies, significantly lower ratios of TF-specific IgG/IgM and IgG/IgA, an increased SNA reactivity of anti-TF antibodies, mostly on account of IgG, and a lower avidity of TF-specific antibodies, especially their SNA-reactive subset. An increased SNA reactivity of anti-TF IgG was observed already at the early stages of cancer (p = 0.0004). The decrease of the ratio of IgG/IgM and IgG/IgA showed a good accuracy of diagnostics with about 60% sensitivity at 90% specificity. A similar potential was found for the SNA binding/IgG level index. The high level of TF-specific IgA antibodies was associated with a lower survival rate (hazard ratio = 0.34). Conclusion: This is the first report ever on the colon cancer-related signatures of anti-TF antibody diversity which show diagnostic potential, including in early cancer, and prognostic value. The hypersialylation of TF-specific antibodies appeared to be a common phenomenon in cancer. The signatures may be used as non-invasive antibody-based markers for colon cancer.